The association of chronotype on depression in adolescents: the mediating role of sensation seeking and sleep quality - Fangyi Wang; Ying Zhou; Xiao Hou; Shifen Ni; Xiaodi Xia; Tanwei Zhang; Yunyan Zhang; Xiangyu Li; Keyi Wen; Yutong Wang; Wenfen Zhu; Yixiao Fu (BMC Psychiatry)
Abstract Objectives This study explores the relationships among chronotype, sensation seeking, sleep quality and depressive symptoms in adolescents with diagnosed depression, aiming to clarify the mechanisms by which chronotype is associated with depression. Methods This cross-sectional study assessed 216 adolescents with diagnosed depression using a demographic questionnaire, the Morningness-Eveningness Questionnaire, the Sensation Seeking Scale, the Pittsburgh Sleep Quality Index, and the Beck Depression Inventory. Descriptive and correlational analyses were performed using SPSS 27.0, and structural equation modeling was conducted via AMOS to explore the mediating roles of sensation seeking and sleep quality in the relationship between chronotype and depression. Results The study found that 60.6% of adolescents with depression were evening chronotypes. Evening chronotype was associated with higher sensation seeking (r = -0.134, p < 0.05), poorer sleep quality (r = -0.303, p < 0.01), and more severe depressive symptoms (r = -0.376, p < 0.01). Chronotype showed a direct effect on depressive symptoms (effect size = -0.318, 95% CI = -0.602 to -0.049, p < 0.05) and an indirect effect via sleep quality, accounting for 80.5% of the total effect. While sensation seeking alone was not a significant mediator, it contributed to a chain mediation with sleep quality, accounting for 13% of the total effect (combined effect size = -0.053, 95% CI = -0.163 to -0.005, p < 0.01). Conclusions Chronotype may play a significant role in adolescent depression, with both direct and indirect effects mediated by sleep quality and sensation seeking. The findings highlight the potential importance of sleep quality as a mediating factor, indicating that interventions targeting sleep improvement could be a promising avenue for further exploration in alleviating depressive symptoms in adolescents.